Ownership Concentration and Debt Structure: Evidence from Top 100 PLCs in Malaysia - Neshaleni, S. Paramanantham; Irene, Wei Kiong Ting; Qian, Long Kweh (University of Malaya, 2018)
This study examines the impact of ownership concentration on debt structure. Based on market capitalisation, we obtained financial and governance data from Top 100 public listed companies in Malaysia for the period 2011-2015. Ordinary least squares and fixed-effect panel models were employed for examining data. The regression results showed that ownership held by the top five shareholders significantly and negatively affected long term debt and total debt ratios. The results remain qualitatively similar in both estimations using the ordinary least squares and fixed-effect panel models. In summary, this study offers some insights into how concentrated ownership influence corporate debt structure.